Estimating Direct Waves with Respect to Receiver Offset, Antenna Current and Frequency in MCSEM - Nyamasvisva, T.E. (Institute of Electrical and Electronics Engineers Inc., 2016)
Marine controlled source electromagnetics is a relatively new de-risking method in hydrocarbon surveys. Normally undertaken as a confirmation or supplementary process to the seismic methods, this process often is applied in offshore environments. It enhances the decision-making process in offshore oil fields minimizing risk analysis associated with the uncertainties present in the oil and gas searching process. Such uncertainties may lead to losses of hundreds, even thousands, of millions of dollars in missed target or false target drilling. To reduce this risk major components of the received data from the subsurface have to be studied, evaluated, quantified and eliminated before decisions are made. One such this data component is the direct wave from the transmitting device directly to the receiver. This paper proposes an assisted methodology to quantify direct waves as a function of the transmitting current of the antenna, antenna frequency with respect to offset of the receiver from the antenna. To do so, first comprehensive simulations of related scenarios were developed and analyzed. A mathematical function was developed to model the representativeness of a specific model to an actual sea bed logging environment. Then, the mathematical model was validated with a blind data set to measure its accuracy. Â© 2016 IEEE.